KUALITAS GURU MENGAJAR SEBAGAI SALAH SATU UPAYA MENINGKATKAN STATUS AKREDITASI SEKOLAH - Khotimah, Husnul; Harapan, Edi; Kesumawati, Nila (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This study determined 1) the quality of teaching teachers in SD Negeri 18 Tanjung Raja; and 2) how much is the contribution of the quality of teaching teachers in an effort to improve the status of school accreditation. The sample in this study were 11 teachers. Data collection techniques were 1) interviews, 2) observation, and 3) documentation. Data analysis techniques were 1) data reduction, 2) data presentation, and 3) data verification. The results of this study indicate that the quality of teaching teachers at SD Negeri 18 Tanjung Raja is in the good category and the quality of teachers who teach contributes to improve the accreditation status of schools at SD Negeri 18 Tanjung Raja.